ChemInform Abstract: Recyclable and Selective Nitroarene Hydrogenation Catalysts Based on Carbon‐Coated Cobalt Oxide Nanoparticles. Issue 31 (14th July 2016) - Chen, Bingfeng; Li, Fengbo; Huang, Zhijun; Yuan, Guoqing
Abstract: A title new nanoparticles are synthesized and characterized.